Crop diversification with short-duration cassava (Manihot esculenta) in the humid tropics for agronomic and economic benefits - SUJA, G; SREEKUMAR, J (The Indian Journal of Agricultural Sciences, 2015)
Presently cassava (Manihot esculenta Crantz) cultivation has shifted from the uplands to the lowlands, sequentially after main crop of rice, banana or vegetables and short-duration varieties (6-7 months) hold great promise. A three-year field experiment was carried out during 2007 to 2010 at Central Tuber Crops Research Institute, Thiruvananthapuram to develop feasible short-duration cassava-legume system in lowland situation akin to rice fallow. Two short-duration cassava varieties, Vellayani Hraswa and Sree Vijaya were evaluated in two cropping systems (sequential cropping and intercropping) involving two types of cowpea (vegetable (var. Pusa Komal) and grain types (var. C 152)) under two fertility levels based on soil testing (full and reduced) in split plot design. Vellayani Hraswa (24.55 tonnes/ha) produced significantly higher yield over Sree Vijaya (21.46 tonnes/ha) in systems involving cowpea. But the tuber and total biomass, crop growth rate, tuber bulking rate, mean tuber bulking rate, relative growth rate and harvest index of the varieties was comparable. Sequential cropping proved superior to intercropping as indicated by the significantly higher fresh tuber yield of 26.07 tonnes/ha under sequential cropping over 19.94 tonnes/ha in intercropping) and dry matter production. Both vegetable cowpea and grain cowpea were equally compatible with short-duration cassava under both the systems. Entire P and half N for short-duration cassava (N: P2O5: K2O @ 50:0:100 kg/ha) could be saved in both the systems involving cowpea by the third year. Sequential cropping of vegetable cowpea [Vigna unguiculata (L.) Walp.] followed by short-duration cassava (under full N) proved to be a profitable production system generating the highest net return (Rs. 97398/ha) and benefit: cost ratio (2.15).